Commercialization of orange- eshed sweetpotato based products in Malawi - International Potato Center (2017)
The international Potato Center (CIP) is promoting Orange-fleshed Sweetpotato (OFSP) production, consumption and marketing as an easily accessible source of vitamin A to tackle to vitamin A deficiency (VAD) especially among under five children, pregnant women and lactating mothers in Malawi. CIP has advanced its partnership with public and private institutions in promoting and expanding production and commercialization of OFSP across value chains.